Improvement plan for linguist competence. A school linguistic project - Gómez Vidal, Antonia; Arcos Cañete, Diego (Avances en Supervisión Educativa, 2007)
The educative experience explained in this article stems from the application of the so-called "diagnostic evaluation" tests in Andalusian secondary schools during the 2006/07 academic year. Its aim is to facilitate a set of initiatives to improve our students' linguistic competence. This competence is considered a key element so as to achieve successful learning and subsequent personal development. The project has been accepted and implemented by the entire teaching staff since all of them are distinctly convinced that the improvement of such a competence does not exclusively depend on the Spanish Language and Literature Department. The project is consequently being developed in any subject or area of the secondary education curriculum without compromising the integrity of the academic content.